Strengthening mechanisms of (Al3Zrmp + ZrB2np)/AA5052 hybrid composites. (December 2016) - Gautam, G; Kumar, N; Mohan, A; Gautam, RK; Mohan, S
To establish the correlation between grain size, dislocations, dispersed particles (size and vol.%) along with their solid solution strengthening effects in alloy and combined effect of all on the strengthening of advanced composite materials (Al3 Zrmp  + ZrB2np )/AA5052 hybrid composites have been selected for the investigation. (Al3 Zrmp  + ZrB2np )/AA5052 hybrid composites have been synthesized by the direct melt reaction of AA5052 alloy and inorganic salts (K2 ZrF6 and KBF4 ). These composites have been characterised by X-ray diffractometer, optical microscopy, scanning-electron microscopy with energy-dispersive spectroscopy, transmission-electron microscopy, tensile and hardness test. Results indicate the successful formation of second phase reinforcement particles namely Al3 Zr and ZrB2 in the AA5052 alloy matrix. Al3 Zr particles exhibit rectangular and polyhedron morphology within an average of micron size while ZrB2 show hexagonal and rectangular within an average of nano size. Grain refinement of Al-rich phase observed in the composites, increases with increasing vol.% of reinforcement particles. TEM observation shows the presence of dislocations in the composite matrix which help to improve the strength parameters. Tensile results show the improvement in strength parameters which improve with the increasing amount of particles whereas percentage elongation also improves up to certain vol.% of particles and beyond that decrease. However, bulk hardness shows an increasing trend continuously with vol.% of particles. The strengthening mechanisms, namely dislocation, Orowan, grain-refined and solid solution are quantified for the hybrid (Al3 Zrmp  + ZrB2np )/AA5052 composites and the total of above are in agreement with experimental results. Solid-solution and Orowan are the predominant strengthening mechanisms in the composites.